An electronic tool for health systems to assess and communicate discharge medication access. (12th October 2021) - Griebe, Kristin M; Hencken, Laura N; Efta, Jessica; Patel, Nisha; Stine, John J; Bott, Brandon; El-Khoury, Caren; MacDonald, Nancy C
Abstract: Purpose: The purpose of this study was to describe how the discharge medication cost inquiry (DMCI) consult order and workflow were created and used to communicate transition of care needs and medication access barriers before discharge. Summary: Health-system pharmacists collaborated with the information technology department to develop the DMCI consult order and workflow. This institutional review board–approved retrospective case study evaluated use of the DMCI consult order throughout the health system. Outcomes that could not be retrieved electronically were collected for every third patient encounter using manual chart review. The DMCI consult order was used at each hospital in the health system. Physicians placed the most DMCI consult orders; however, pharmacists at the large academic tertiary hospital utilized the DMCI consult order the most. The DMCI consult order was sent most frequently for anticoagulants. Although most medications were covered by insurance, the tool and workflow identified barriers to medication access. Almost 90% of the patients with a DMCI consult order had at least one prescription generated on discharge. Conclusion: The DMCI consult order is a novel electronic tool to aid in communicating discharge medication needs. When incorporated into care transition planning, the DMCI consult order and workflow provide a model to ensure patients have access to medications. It can also be used to document and evaluate the role of pharmacy in transitions of care in the health system.